2005
DOI: 10.1161/01.res.0000186522.89544.4d
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of α-Lipoic Acid in Lipopolysaccharide-Induced Endothelial Fractalkine Expression

Abstract: Abstract-Fractalkine is a unique chemokine that functions as a chemoattractant as well as an adhesion molecule on endothelial cells activated by proinflammatory cytokines. Alpha-lipoic acid (LA), a naturally occurring dithiol compound, is an essential cofactor for mitochondrial bioenergetic enzymes. LA improves glycemic control, reduces diabetic polyneuropathies, and mitigates toxicity associated with heavy metal poisoning. The effects of LA on processes associated with sepsis, however, are unknown. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 31 publications
8
50
0
Order By: Relevance
“…Taking together our present results in cultured adipocytes and previous data of other groups in Hep G2 [46,23] and HUVEC [45] cells suggest a role of Sp1 in mediating some of the actions observed for LA in in vitro models. However, it still remains to be addressed the potential physiological involvement of Sp1 in the effects of LA after dietary supplementation in animal models.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Taking together our present results in cultured adipocytes and previous data of other groups in Hep G2 [46,23] and HUVEC [45] cells suggest a role of Sp1 in mediating some of the actions observed for LA in in vitro models. However, it still remains to be addressed the potential physiological involvement of Sp1 in the effects of LA after dietary supplementation in animal models.…”
Section: Discussionsupporting
confidence: 89%
“…Our results demonstrated that LA treatment (250 μM for 24 h) inhibited Sp1-DNA binding activity in mature 3T3-L1 adipocytes. In support of these data, a previous study demonstrated that LA decreased the TNF-α and or IL-1β-induced Sp1 binding activity in human umbilical vein endothelial cells [45]. Moreover, a recent trial has also observed that LA inhibited in a dose-dependent manner the activation of Sp1 binding induced by TGF-β in HepG2 cells [46].…”
Section: Discussionsupporting
confidence: 62%
“…Although increased concentrations of these aforementioned proinflammatory mediators play an important role in sepsis, data on fractalkine levels in sepsis were unavailable. Sung et al described how TNF-α and IL-1β stimulate fractalkine release peaking at 4-6 h after stimulation with a steady decline in fractalkine concentrations thereafter (37). Five hours after CLP, plasma levels were slightly elevated compared with sham operated animals.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used 10 ng/ml of TNF-α in accordance with our previous work (17). To investigate the effect of JAK3 inhibition on the TNF-α-induced expression of ICAM-1, VCAM-1, and fractalkine, HUVECs were pretreated with JANEX-1 for 30 min and then incubated with TNF-α for 6 h. Western blot analyses revealed that TNF-α significantly increased the levels of ICAM-1, VCAM-1, and fractalkine proteins relative to the levels observed in the control samples.…”
Section: Inhibition Of Jak3 Reduces Tnf-α-induced Expression Of Cell mentioning
confidence: 99%